PENGARUH PENGHARGAAN FINANSIAL, GENDER, LINGKUNGAN KERJA DAN PERSEPSI TERHADAP MINAT MENJADI AKUNTAN PEMERINTAH - Hartati Hartati; Risni Nelvia (Jurnal Manajemen Sains, 2022)
Interest is a condition where the individual pays more attention to something and is accompanied by his desire to know and learn and prove more about the situation. This study aims to determine the effect of financial rewards, gender, work environment and perceptions on student interest in becoming Government Accountants. This study uses primary data by distributing questionnaires to students of the Accounting Study Program at Muara Bungo University class 2018-2019 with a population of 75 students. The sample in this study amounted to 69 students who were obtained using a saturated sampling technique. The results showed that the level of financial appreciation, gender and work environment partially had no effect on students' interest in becoming Government Accountants, perceptions partially influenced students' understanding of interest in becoming Government Accountants. The value of the coefficient of determination (Adjusted R Square) is 0.282. This result means that there is a contribution of 28.2% (low) from the variables studied. While the remaining 71.8% is influenced by other variables not examined in this study.